2019
DOI: 10.1142/s2424786319500014
|View full text |Cite
|
Sign up to set email alerts
|

The general dynamic risk assessment for the enterprise by the hologram approach in financial technology

Abstract: The purpose of this paper is to discuss the general risk assessment under the Hologram framework for the enterprise based on big data language; and to illustrate the Hologram as a new tool for establishing a mechanism to evaluate SMEs growth and change in financial technology dynamically (here we mainly focus on SMEs as they are one of the very important classes for enterprises with less information available from financial accounting report and associated assets. Indeed, the approach discussed here is applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Actually, in network environment it has been widely found that SMEs by no means operate independently, but cooperate in groups and form symbiotic relationships with strategic partners by joining resources to achieve common goals, gain competitive advantage, and even share risks. 22,23 Furthermore, in the development process there exist nonstrategic partners, which are numerous and often replaceable. The instable relationships between nonstrategic partners and focused SME are created temporarily, and only exist in certain time periods as required, which leads to the fluctuating number of nonstrategic partners with the time.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Actually, in network environment it has been widely found that SMEs by no means operate independently, but cooperate in groups and form symbiotic relationships with strategic partners by joining resources to achieve common goals, gain competitive advantage, and even share risks. 22,23 Furthermore, in the development process there exist nonstrategic partners, which are numerous and often replaceable. The instable relationships between nonstrategic partners and focused SME are created temporarily, and only exist in certain time periods as required, which leads to the fluctuating number of nonstrategic partners with the time.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of SMEs acting as outward investors cannot be neglected in the process of growth, and the investment process inevitably results in the active or negative influence on state evolution. Therefore, we are motivated to employ the dichotomous process 24 to mimic the outward investment influence on damping effect, and the typical model, only with additive risk, 22,23 is extended to the generalized form with both internal additive risk and external multiplicative risk. In essence, it is based on Schumpeter's economic thought for economic development theory with the "innovation" being an internal factor, and the "economic development" being a change of economic life from internal creativity applying to the SME growth in the tech-economic paradigm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al [ 34 ] uses big data technology to analyze customers' browsing behaviors, habits and hobbies, so as to help enterprises understand customers' needs more clearly and provide customers with efficient and accurate services. With the help of "hologram", Yuan et al [ 35 ] provides a new method to evaluate enterprise credit risk based on business behavior interaction. Although the emergence and application of emerging technologies such as the Internet of things and big data, supply chain finance can’t be divorced from credit risk.…”
Section: Discussionmentioning
confidence: 99%